Perlindungan Form Website Pada Framework Flask Dengan Metode Regular Expression - Mahendra Chevro Susanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This research aims to find out the use of regular expression methods in protecting website forms on the flask framework. The regular expression pattern used in this research is [^A-Za-z0-9@]. In this study, testing was carried out using the black box testing method Equivalence Partitioning technique to create test criteria in website form input. The results of black box testing produce two expectations, namely